A high preoperative carbohydrate antigen 19-9 level is a risk factor for recurrence in stage II colorectal cancer. (3rd June 2017) - Nozawa, Hiroaki; Ishihara, Soichiro; Kawai, Kazushige; Hata, Keisuke; Kiyomatsu, Tomomichi; Tanaka, Toshiaki; Nishikawa, Takeshi; Otani, Kensuke; Yasuda, Koji; Sasaki, Kazuhito; Murono, Koji; Watanabe, Toshiaki
Abstract: Background: Many risk factors for recurrence in stage II colorectal cancer (CRC) have been proposed, and the efficacy of adjuvant chemotherapy is still controversial. This study aimed to identify risk factors for tumor recurrence and assess whether they are related to the benefits of adjuvant chemotherapy in stage II CRC. Material and methods: Patients with stage II CRC that was curatively operated on in a tertiary hospital between 2005 and 2014 were analyzed. Cox's proportional hazards models were applied to identify risk factors for recurrence and overall mortality. Kaplan-Meier methods were used to evaluate whether adjuvant chemotherapy was beneficial in terms of recurrence-free survival (RFS). Results: A total of 384 patients were identified, among whom 38 (10%) received adjuvant chemotherapy. In a median follow-up of 48.6 months, 52 patients (14%) developed recurrence. Multivariate analyses identified two independent parameters that significantly decreased RFS; pathological T4 [hazard ratio (HR), 2.34; 95% confidence interval (CI), 1.31–4.15; p = .0045) and preoperative carbohydrate antigen (CA) 19-9 > 37 U/ml (HR 1.96; 95% CI 1.02–3.58; p = .045). These factors also inversely correlated with overall survival; T4: HR 2.10, p = .019) and CA 19-9 > 37 U/ml (HR 2.15, p = .025). The combination of T4 and CA 19-9 > 37 U/ml resulted in an increased HR (3.52) for recurrence. However, adjuvant chemotherapy did not improve RFS in patients with these features. Conclusion: The present study demonstrated elevated CA 19-9 levels as well as T4 independently predicted worse long-term outcomes in patients with stage II CRC. However, the characterization of patients who gain survival advantages by adjuvant chemotherapy requires further investigation.